2017
DOI: 10.1016/j.ajo.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of the Peripapillary Retina in Primary Angle-Closure Glaucoma

Abstract: In acute PACG eyes, peripapillary retinal VD decreased significantly compared with the contralateral unaffected eyes. Peripapillary retinal VD was significantly correlated with other glaucomatous changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
79
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 30 publications
14
79
1
1
Order By: Relevance
“…Comparison between the two eyes showed that the eyes with a condition post-acute primary angle closure had significantly lower peripapillary VD than the contralateral eyes. 31,32 Suwan and coworkers 33 deal with the topic of peripapillary blood flow measured by OCTA in exfoliation syndrome, XFG and POAG compared with healthy eyes. The blood flow was calculated using MATLAB software (The Mathworks, Inc., Natick, MA, USA) and perfused capillary density (PCD).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between the two eyes showed that the eyes with a condition post-acute primary angle closure had significantly lower peripapillary VD than the contralateral eyes. 31,32 Suwan and coworkers 33 deal with the topic of peripapillary blood flow measured by OCTA in exfoliation syndrome, XFG and POAG compared with healthy eyes. The blood flow was calculated using MATLAB software (The Mathworks, Inc., Natick, MA, USA) and perfused capillary density (PCD).…”
Section: Discussionmentioning
confidence: 99%
“…Retinal vasculature plays a crucial role in the pathogenesis of both acute and chronic glaucoma. Several independent studies have reported decreased retinal blood flow and capillary density in patients with open-angle and angle-close glaucoma (4)(5)(6)(7)(8)(9)(10). In animal model of retinal I/ R, significant vascular leakage and disruption were observed a few hours after injury (11), whereas capillary degeneration was detected about 7 d later (12,13).…”
mentioning
confidence: 99%
“…This study was approved by the Institutional Review Board of Peking Union Medical College Hospital Sep. in 2016 were enrolled. The inclusion and exclusion criteria refer to the principles decribed in our previous study [11] . Table 1.The significant differences were found on these parameters between two groups except for IOP, this could be due to a proper treatment after APAC attack.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we have reported peripapillary retinal vessel density (RVD) was lower after APAC [11] . Sequentially, the purpose of this study was to investigate macular perfusion with OCTA and evaluate the potential relationship of MVD measurements with other glaucomatous structure and function changes in PACG after APAC.…”
Section: Introductionmentioning
confidence: 95%